مناسك الحج: لأبي الجسن علي بن محمد بن بركة التطواني الأندلسي (1120هـ) دراسة وتحقيق (Journal of Humanitarian and Applied Sciences, 2023)
Many Al-Maliki scholars are interested in the provisions of the Hajj, as it is one of the five pillars of Islam, and some of them even singled it out for authorship, such as the prosaic, the regulated, the lengthy and the abbreviated. Among those scholars who were familiar with the rituals, Sheik: “Abu Al-Hasan Ali Bin Mohammed Baraka Al-Tatwani”: nicknamed: "Haj Baraka Al-Andalusi Al- Tatwani" (1120H). The term “Sheik” was distinguished for its easiness and conciseness, understood by the general public, and it does not need to be explained. It represents the gest of the Hajj and Umrah works in short, as he limited himself to a statement of the full and best character according to Al-Malikiyah's famous quotation in most Hajj works. He also defined some of the juristic terms that need to be clarified, including: "The committed: which is between the Black Stone and the door." In my work, I have relied on a number of jurisprudential approaches, including the descriptive approach to the description of the author and its contents. I have also adopted the documentary approach: In the attribution of transcripts, sayings, and the production of scriptures and narratives. I also used the analytical method: in analysing the author's speech, and commenting on it. The Sheik's rituals turned out to be based on evidence, as he rooted many jurisprudence issues related to the pilgrimage, disciplined by the most famous of the school and ease of expression.
Keywords: Rites; Hajj; Al-Tatwani; Umrah (minor hajj); Rites, Hajj, Umrah (minor hajj), Al-Tatwani, ransom